The p38α mitogen-activated protein kinase as a central nervous system drug discovery target - Van Eldik Linda J; de Almeida Lucia; Borders Aaron S; Watterson D Martin (BMC Neuroscience, 2008)
Abstract Protein kinases are critical modulators of a variety of cellular signal transduction pathways, and abnormal phosphorylation events can be a cause or contributor to disease progression in a variety of disorders. This has led to the emergence of protein kinases as an important new class of drug targets for small molecule therapeutics. A serine/threonine protein kinase, p38α mitogen-activated protein kinase (MAPK), is an established therapeutic target for peripheral inflammatory disorders because of its critical role in regulation of proinflammatory cytokine production. There is increasing evidence that p38α MAPK is also an important regulator of proinflammatory cytokine levels in the central nervous system, raising the possibility that the kinase may be a drug discovery target for central nervous system disorders where cytokine overproduction contributes to disease progression. Development of bioavailable, central nervous system-penetrant p38α MAPK inhibitors provides the required foundation for drug discovery campaigns targeting p38α MAPK in neurodegenerative disorders.